Retrosynthesis and its application: Problem solving approach - Satyaban Jena; Rout, Laxmidhar (New Delhi: Indu book service, 2024)
There are six chapters in the book starting from scratch to complex level. Chapter 1 is started with basics of Retrosynthesis explaining tricks of disconnection. Chapter 2 deals with retrosynthesis of analgesics, whereas chapter 3 is related to synthesis of pesticides. Chapter 4 covers Retrosynthesis of Anthelmintic, Tranquilizer, Antiasthmatics. Chapter 5 cover retrosynthesis of Antibiotic and the final chapter 6 is devoted for Synthesis of Common Natural Products and medicines. A total of 120 natural product and common medicines were covered in the book.
Includes appendix
Keywords: Retrosynthetic analysis -- Organic synthesis -- Reaction mechanisms